Developing a synchronous otolaryngology telemedicine Clinic: Prospective study to assess fidelity and diagnostic concordance. (27th October 2017) - Seim, Nolan B.; Philips, Ramez H. W.; Matrka, Laura A.; Locklear, Brittany; Inman, Mark; Moberly, Aaron C.; Essig, Garth F.
Abstract : Objective: To evaluate diagnostic concordance of a synchronous telemedicine otolaryngology clinic with use of currently available technology. Study Design: Prospective. Methods: Patients in a rural otolaryngology clinic were enrolled in a pilot telemedicine clinic. To assess system fidelity, an on‐site and remote (consulting) otolaryngologist conducted simultaneous patient evaluations using streaming telecommunication technology for all aspects of the clinical encounter, including high‐definition examination and endoscopic images. Both physicians and patients were blinded and diagnoses recorded. Post‐encounter physician surveys and an original patient‐centered TeleENT Satisfaction Questionnaire (TESQ) were used to assess overall satisfaction. Results: Twenty‐one patients were enrolled consecutively. Visual technology was found acceptable in all cases, and audio technology was acceptable in 20 of 21 encounters. Patient satisfaction was 96%, and patients felt comfortable using a telemedicine system in the future. Encounters were not significantly longer than traditional encounters. Physician diagnostic agreement was found in 95% of cases, and the consulting physician indicated that all encounters provided sufficient history, examination, and high‐quality images to generate an accurate diagnosis, order additional workup, and/or make an appropriate referral. Conclusion: A synchronous otolaryngology telemedicine clinic is comparable to a standard clinic in terms of diagnostic concordance and patient satisfaction when using streaming technology and high‐definition images. Using telemedical technology may be a viable way to increase otolaryngology access in remote or underserved areas. With system validity now established, future studies will assess the feasibility of using trained on‐site physician extenders (nurse practitioners or physician assistants) to conduct in‐person patient encounters with remote otolaryngologist support. Level of Evidence: 2c. Laryngoscope, 128:1068–1074, 2018